Adoption of Roguing to Contain Banana Bunchy Top Disease in South-East Bénin: Role of Farmers' Knowledge and Perception. Issue 4 (1st October 2020) - Abiola, A.; Zandjanakou-Tachin, M.; Aoudji, K. N. A.; Avocevou-Ayisso, C.; Kumar, P. Lava
ABSTRACT: Banana bunchy top disease (BBTD) caused by Banana Bunchy Top Virus (BBTV) has emerged as a major constraint of banana and plantain production in south-East Bénin. Roguing method is used in this area to destroy the BBTV-infected plants and to contain its spread. This study was conducted to assess the level of adoption of the method in relation to farmers' perception. The research was conducted in eight communities and data collected from 186 randomly selected banana growers. Farmers' perception on the roguing method as compared to traditional practices was analyzed using an aggregated perception index. The counterfactual method based on Average Treatment Effect was used to estimate adoption rates and determine the factors influencing adoption. Results showed that roguing is perceived to provide more advantages than traditional practices, but it is often time consuming and very labor demanding. The actual adoption rate is 36%. It would have been 56% if all the growers sampled were sensitized. As a matter of fact, the majority (73%) of sensitized growers adopted the method. More efforts and resources should be put into sensitizing and mobilizing farmers on the adoption of this technology while improving its efficiency and taking account the shortcomings reported by farmers. This, coupled with an increase in easy access to healthy planting materials and use of good production practices could improve the adoption of roguing and consequently ensure the effective containment of BBTD.